Pengaruh Gaya Kepemimpinan Otoriter dan Kompetensi Terhadap Prestasi Kerja Karyawan Pada PT Wira Karya Teknik Konsultan Palembang - Khalily, Muhammad Naufal; Roswaty; Kurniawan, Mohammad (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET) - Lembaga KITA, 2023)
This study aims to analyze the effect of authoritarian leadership style and competence on the performance of employees of PT Konsultan Wira Karya Teknik Konsultan Palembang. The objects in this study were all 40 employees of PT Wira Karya Teknik Konsultan Palembang. The analysis technique used was multiple analysis which was processed with the help of the SPSS version 22 computer program. This study used a sampling technique by means of saturated sampling. The sample in this study is to take all the population as many as 40 samples. Collecting data using questionnaires and interviews. The analysis technique used was multiple analysis which was processed with the help of the SPSS version 22 computer program. The results of the study found that using the t test on authoritarian leadership style had a positive and significant effect on work performance with a value of 3.376 > 2.026 with a significance of 0.002 <0.05. Competence has a positive and significant effect on work performance with a value of 2.116 > 2.026 with a significance of 0.041 < 0.05. Based on the results of the multiple regression coefficient test, the final equation is Y = 5,000 + 0,468 X1 + 0,311 X2 + e. Based on the results of the calculation of the coefficient of determination (R2), it is known that the influence of authoritarian leadership style and competence on employee performance at PT Wira Karya Teknik Konsultan Palembang is 46.5%, and based on the calculation results of the F hypothesis test is accepted so that the hypothesis Ha is accepted which is in a strong correlation with Fcount > Ftable (16,090 > 3.25), or in other words, there is an influence of authoritarian leadership style and competence on employee performance at PT Wira Karya Teknik Konsultan Palembang.